The Effect of Organizational Commitment and Job Satisfaction on Work Discipline in Employees of the Regional Revenue Agency (BAPENDA) Donggala Regency - Qosim, Nanang (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
The test results above show, where the constant value of 3.277 is a fixed number which means that there is an influence of organizational commitment and job satisfaction on the discipline of employees of the Regional Revenue Agency (BAPENDA) Donggala Regency. Furthermore, the regression coefficient of the organizational commitment factor (X1) of 0.385 means that if there is a change in X1 by one unit, there will also be a change in employee discipline of the Regional Revenue Agency (BAPENDA) of Donggala Regency by 0.385 and assuming organizational commitment increases by one unit and other variables remain, employee discipline increases by 0.385. The coefficient regression of job satisfaction factors means that there is an influence of 0.342 on the discipline of employees of the Regional Revenue Agency (BAPENDA) of Donggala Regency. Multiple or correlation coefficient (R) is the relationship between the two independent variables, namely organizational commitment and job satisfaction with employee discipline of 0.529, meaning that the relationship of the independent variable to the dependent variable is strong. R Square or coefficient of determination (R2) is to see the influence between the variables of organizational commitment and job satisfaction on employee discipline by 0.280 or 28%, meaning the influence of the independent variable (independent) on the dependent variable (dependent). While the remaining 72% is the influence of other variables that were not studied in this study.